Taste-Aroma-Matrix Interactions Determine Flavour Perception - Hollowood, Tracey Ann (2002)
A newly recruited sensory panel was trained in magnitude estimation and time intensity sensory techniques. Sensory analysis was combined with instrumental analysis using MS Nose to investigate the relationship between stimulus and perception using simple model food systems.